A voyage of discovery to the North Pacific Ocean, and round the world : in which the coast of north-west America has been carefully examined and accurately surveyed : Undertaken by His Majesty's command, principally with a view to ascertain the existence of any navigable communication between the North Pacific and North Atlantic Oceans, and performed in the years 1790, 1791, 1792, 1793, 1794, and 1795, in the Discovery sloop of war, and armed tender Chatham, under the command of Captain George Vancouver : in three volumes, Vol. II. - Vancouver, George, 1757-1798.; Guerra, Francisco, 1916- , ant. pos. BHI BH FG 2742.; Warner, J., fl.1811, il.; Alexander, William, 1767-1816, il.; Fittler, James, 1758-1835, il.; Pouncy, Benjamin Thomas, d.1799, il.; Edwards, John, fl.1798, imp. (Londres); Robinson, John., fl.1781-1806, imp. (Londres); Robinson, Georges G., imp. (Londres); Vancouver, John, m.1828?, ed. lit. (London : printed for G.G. and J. Robinson . and J. Edwards, 1798)
Mode of access: Internet. Editado por John Vancouver según consta en la Advertencia del editor del T. I. Los grabados calcográficos: I. The mission of St. Carlos near Monterrey (p. 10). II. Chart of Hergerst's Islands (p. 94). III. Salmon Cove, Observatory inlet (p. 332). IV. The new Eddystone in Behm's canal (p. 352). V. The Presidio of Monterrey (p. 440). Todas los grabados dibujados por W. Alexander y grabados por B.T. Pouncy y J. Fittler, el mapa grabado por J. Warner. Sign.: [A]-2Z4, 3A-3S4.